Modeling certain digital atlas map elements from the geographical information systems aspect - Stamenković, Nikola S.; Bakrač, Saša T.; Milanović, Miško M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Besides geographic maps, atlases represent the most important cartographic models of environment. Nowadays, contemporary geographic information systems (GIS)are increasingly used ' in planning, designing and predicting the conditions and processes of complex dynamic spatial systems. Collecting data and information for a specific geographical map and GIS represents its basis. Modeling of mathematical elements One of the conditions for a successful development of an atlas is to define the preliminary mathematical elements of atlas maps. The mathematical basis of the atlas consists of the following mathematical elements: geodetic base, map projection, grid, a framework map and a scale. Descriptions and analyses of the mathematical basis of cartographic sources for the development of digital atlas geographic mapslead towards the unity and uniformity of a new atlas geodetic base and towards reducing differences in the use of different projections in display of collected spatial data. For modeling one atlas, numerous cartographic sources from differentepochs are used. Spatial databases and GISs One of the most important parts of each GIS are related databases as well as defining their structure and content. The challenges facing cartography, related to the content and structure of spatial databases, concern mostly the issues of generalization and visualization of spatial relations in a particular thematic map. One of the requirements set when creating atlases and enabling a later analysis of the data presented as an entity is also a requirement for enabling an object-oriented approach to problem solving, which requires the existence of an object-based GIS software. Geographic atlas content and GIS preprocessing Geographical atlas maps elements can be conditionally divided into four groups, and shown within the following items: topographic, hydrological, geological-lithological and supporting or informative groups. Preprocessing in a GIS involves the processing and preparation of all external spatial databases that can be used to create basic, general and other atlas maps. Processing of available data refers to customizing the data appearance, form and structure for use within a desired GIS software. Structuring digital atlas maps supported by the GIS Structuring atlas maps depends closely on and is related to the contemporary way of making digital maps and to the traditional cartographic method. Structuring digital atlas maps includes registration and transformation of data and the formation of digital models and maps. Forming certain digital models and thematic maps implies not only the current map design in order to assign certain colors and shades to the map or define the line thickness, size, layout and type of letters and numbers, but it also includes consideration of the overall look of the map, its readability and mental impressions that may leave on the user. Using a specific methodology ienables successful modeling of digital atlas maps within geographical information systems. This implies defining the basic mathematical elements of digital atlas maps, the possible structure and form of spatial databases as a part of a geographical information system used in modeling.
Keywords: modeling; atlas maps; geographical information systems